The identification and characterisation of disease genes in craniosynostosis - Fenwick, AL (2015)
Current challenges to the understanding and clinical management of craniosynostosis (premature fusion of the cranial sutures) include the interpretation of changes in known disease genes, the identification of novel disease genes and the identification of pathogenic regulatory mutations. This thesis aims to address these issues and by doing so improve diagnosis, surgical prognosis and support for affected families. Expanding the repertoire of known disease mechanisms, pathogenicity of an apparently synonymous substitution in FGFR2 is demonstrated, associated with a mild Crouzon syndrome phenotype. Furthermore, a new severe phenotype associated with localised mutations in TWIST1 (usually associated with Saethre-Chotzen syndrome; SCS) is described. In an attempt to better understand the underlying pathogenesis of SCS, six probands with a clinical diagnosis, but no TWIST1 mutations, underwent whole-genome sequencing. Two individuals were found to have mutations in TCF12, a dimerization partner of TWIST1, and one patient had compound heterozygous mutations in CDC45. The latter, however, was not initially prioritised as one of the mutations led to a silent substitution, and this individual also had a de novo variant in a gene that interacts with a known craniosynostosis pathway. To further explore the contribution of regulatory mutations to the pathogenesis of SCS, targeted sequencing of a 2.4 Mb region around TWIST1, and 640 kb around TCF12, was undertaken on DNA from 160 coronal synostosis patients. As well as coding mutations that had been missed, intronic splicing mutations and putative TWIST1 promoter mutations were identified. In summary, during the course of this work novel and sometimes unexpected pathogenic mechanisms of mutations both in previously known genes (FGFR2, TWIST1) and in newly defined genes (TCF12, CDC45) have been identified. The pathogenicity of apparently synonymous variants provides important lessons in the correct interpretation of patient sequence data, and the identification of novel disease genes expands the classification and range of pathophysiology in craniosynostosis.